History of the semantic evolution of the concept of revolution and its impact on the birth of political Islam - Hamid Yahyavi; soheila rahimi (رهیافتهای سیاسی و بین المللی)
The present study is an attempt to set forth a new understanding of contemporary political thought in Iran with a focus on the semantic transformations of concepts and their political implications. The theoretical framework used in the present paper is Reinhart Kozelck’s conceptualization of the “history of concepts”’, which have been visible as implications of linguistic turn for historical sciences. Accordingly, the paper would examine the history of the semantic transformation of the concept of revolution as one of the most important concepts in contemporary political thought in Iran, in order to shed light on the birth of political Islam in contemporary Iran. ‘How the introduction and transformation of the meaning of revolution into the system of concepts of Islam led to the transformation of the meaning of other Shiite earlier concepts?’ This is the main question that guides the analytical narration in the research. The paper hypothesizes that due to the formation of a new semantic field and the introduction of new concepts such as revolution into the system of Shiite concepts in the contemporary era, new semantic layers were added to Shiite classic concepts such as Entezar (waiting), Taqiyya (precautionary dissimulation), Ijtihad (Interpretation). This transformation in the system of concepts formed a transformation within Shi'a theology which led to the birth of ‘political Islam’ in contemporary Iran.